Seroprevalence and molecular analysis of yellow fever virus in mosquitoes at Namanga and Mutukula borders in Tanzania - Remidius Kamuhabwa Kakulu; Josephine Vitus Kapinga; Sima Rugarabamu; Elison Kemibala; Medard Beyanga; Peter M. Mbelele; Khalid Massa; Esther Gwae Kimaro; Emmanuel Abraham Mpolya (International Journal of Infectious Diseases)
Objectives: Yellow fever (YF) is a major public health concern, particularly in Africa and South America. This study aimed to detect YF in human and mosquito samples to understand transmission dynamics in the Tanzania–Uganda and Tanzania–Kenya cross-border areas. Methods: Blood samples were collected from individuals aged ≥9 months for serological testing. Mosquitoes were captured and tested for YF virus RNA. Logistic regression models were used to predict seroprevalence and associated risk factors. Results: The overall YF seroprevalence was 12.5%, with higher rates among older individuals (7.0%) and female participants (immunoglobulin [Ig] G 4.4%, IgM 6.0%). Notably, YF virus RNA was detected in three out of 46 pools of 192 mosquitoes. The odds of testing positive for YF IgG were lower among those with primary education compared with college education (AOR = 0.27, CI: 0.08-0.88) and increased with those experiencing muscle pain (AOR = 4.5, CI: 1.08-18.78) while the odds of testing positive to YF IgM increased with being female (AOR = 4.7, CI: 1.5-14.7), traveling to YF endemic areas (AOR = 5.2, CI: 1.35-44.75), exposure to Aedes mosquitoes (AOR = 3.7, CI: 1.27-10.84) and exhibiting bruising (AOR = 13.5, CI: 1.23-145.72) Conclusions: Although Tanzania has not experienced YF outbreaks, evidence of YF exposure at the studied borders highlights the need for strengthening cross-border surveillance, vector control, and vaccination efforts. Further research is needed to evaluate the country's overall YF risks.